Diagnostics and technique for the analysis pipelines transportation - Makharadze, L.; Gavasheli, L.; Steryakova S. (Екологія і природокористування, 2012)
The article is discussing an innovative technology for diagnostics and technique for fault detection of the pipelines transportation. The technology has been developed on the basis of the acoustic-emission method for forced response, implying diagnostics of freight pipelines. It will ensure pursuing nondestructive control as well as prompt/precise revealing, classification, definition of the nature, geometrical sizes and location of defects. Acoustic response of both electronics crystalline structures and their phase bonds allows to determine the value of the cyclic crack growth resistance; repeated correlation of the above structures with kinematic diagram of failure make for adequate predicting the remaining life.